Nursing conceptions of teachers about integrality - Rosiane Filipin Rangel; Dirce Stein Backes; Fernanda Demutti Pimpão; Regina Gema Santini Costenaro; Elenice Spagnolo Rodrigues Martins; Grassele Denardini Facin Diefenbach (Rev Rene)
It is a research of descriptive-exploratory character, with a qualitative approach, whose objective is to understand what the Nursing teachers see as integrality. The subjects of the study were seven teachers of a private higher education institution located in the Central Region of Rio Grande do Sul. The data collection was based in the focal group technique, whereby a content analysis technique in the theme modality was used for the data treatment, from which the great theme was obtained: Integrality construction, followed by the subtheme: Continuous process and construction and deconstruction. From the obtained results, it was possible to consider that integrality is a theme under construction, dynamics, it is flexible, passive of new reformulation, based on the experiences and constructions of the subjects themselves. It is concluded that the discussion about integrality encompasses the complexity of being and doing, once it is a process under construction.